Piezoelectric-enhanced triboelectric nanogenerator fabric for biomechanical energy harvesting. (October 2019) - He, Jian; Qian, Shuo; Niu, Xushi; Zhang, Ning; Qian, Jichao; Hou, Xiaojuan; Mu, Jiliang; Geng, Wenping; Chou, Xiujian
Abstract: Flexible and wearable technology, a large trend in recent electronic technology revolution, proposes an urgent demand for the similarly flexible and wearable power supply. Hence a fully flexible and stretchable piezoelectric-enhanced triboelectric nanogenerator fabric (P-TNGF) possessing high output performance, good air permeability and excellent reliability is proposed in this work for human-body movement energy exploiting. Three consecutive energy conversion processes consisting of two triboelectrification processes and one piezoelectric electrification process exist at three different stages of a work period of P-TNGF, which contributes to harvest ambient energy maximally. By the optimization design of uninterrupted energy harvesting in overall process, a maximum open-circuit voltage and short-circuit current of P-TNGF can reach 600 V and 17 μA, respectively, and a maximum output power of 1.11 W/m 2 is obtained experimentally under 20MΩ load. Moreover, the operating capability of P-TNGF in various conditions, such as different stimulation frequency and external contact materials is investigated experimentally, showing excellent reliability and availability. Prepared samples are attached to different human-body parts, such as foot and joints, to demonstrate its wearability and biomechanical energy harvesting capability. Processed by rectification circuit, alternating current generated from P-TNGF are charged into several capacitors with various capacitances, which can be utilized to drive commercial electronic devices. The proposed P-TNGF has great significance for the further development of flexible and wearable technology. Graphical abstract: By the optimization design of three consecutive electrification processes existing in overall working process, the proposed fully flexible and stretchable piezoelectric-enhanced triboelectric nanogenerator fabric has an excellent output performance (VOC = 600 V, ISC = 17 μA), showing broad prospect in flexible electronic field.Image 1 Highlights: A Piezoelectric-enhanced Triboelectric Nanogenerator Fabric is proposed. Three consecutive energy conversion processes exist during a work period. A maximum electrical output of P-TNGF can reach up to 600 V and 17 μA. Capacity of P-TNGF to drive commercial electric devices is demonstrated.